2020
DOI: 10.1038/s41467-020-15538-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved analyses link genomic and immune diversity and reveal unfavorable neutrophil activation in melanoma

Abstract: Complex tumor microenvironmental (TME) features influence the outcome of cancer immunotherapy (IO). Here we perform immunogenomic analyses on 67 intratumor subregions of a PD-1 inhibitor-resistant melanoma tumor and 2 additional metastases arising over 8 years, to characterize TME interactions. We identify spatially distinct evolution of copy number alterations influencing local immune composition. Sub-regions with chromosome 7 gain display a relative lack of leukocyte infiltrate but evidence of neutrophil act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…At the tumour site, one important stromal component is the cancer-associated fibroblasts (CAFs), which have been also shown to promote the activation and survival of neutrophils, of increasing their expression of PDL1, IL8, CCL2 and TNF-, and to turn them into potent inhibitors of T cell functions [65] Locally, not only variations between the different tissue stroma define the nature of TANs, as the genomic and transcriptional landscape of tumours, which can be highly heterogeneous both inter-and intra-lesions, shape the functional state and mobilization of neutrophils. By performing spatially detailed immune and genomic analysis of multiple melanoma primary and metastatic lesions, Mitra et al found a link between the copy number gain of Accepted Article chromosome 7 in melanoma cells and increased infiltration of immunosuppressive neutrophils, which was also associated with increased resistance to checkpoint blockade [66]. Similarly, in breast cancer models, deep immune profiling revealed a dichotomous distribution of myeloid cells distinguishing three discrete groups of tumours: 1) immunologically cold, 2) macrophageenriched, and 3) neutrophil enriched subtypes.…”
Section: Accepted Articlementioning
confidence: 99%
“…At the tumour site, one important stromal component is the cancer-associated fibroblasts (CAFs), which have been also shown to promote the activation and survival of neutrophils, of increasing their expression of PDL1, IL8, CCL2 and TNF-, and to turn them into potent inhibitors of T cell functions [65] Locally, not only variations between the different tissue stroma define the nature of TANs, as the genomic and transcriptional landscape of tumours, which can be highly heterogeneous both inter-and intra-lesions, shape the functional state and mobilization of neutrophils. By performing spatially detailed immune and genomic analysis of multiple melanoma primary and metastatic lesions, Mitra et al found a link between the copy number gain of Accepted Article chromosome 7 in melanoma cells and increased infiltration of immunosuppressive neutrophils, which was also associated with increased resistance to checkpoint blockade [66]. Similarly, in breast cancer models, deep immune profiling revealed a dichotomous distribution of myeloid cells distinguishing three discrete groups of tumours: 1) immunologically cold, 2) macrophageenriched, and 3) neutrophil enriched subtypes.…”
Section: Accepted Articlementioning
confidence: 99%
“…HLA-A2 phenotyping was performed by flow cytometry (clone BB7.2, BD Bioscience). Exvivo stimulation protocol was adapted from a previously described protocol 86 . HLA-A2+…”
Section: Ex-vivo Pbmc Restimulation With Sars-cov-2 Peptidementioning
confidence: 99%
“…Metastatic lesions can evolve divergent molecular states and even within a single tumor mass genetic sub-clones can form spatially distinct regions with different TME composition (Mitra et al, 2020), but how adjacent, genetically heterogeneous regions might influence each other is not well explored. We sought to use Perturb-map to investigate whether neighboring tumors influenced the immune infiltration of one another.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond investigating specific gene functions, Perturb-map also enabled us to examine how specific gene perturbations and associated phenotypes influenced neighboring tumor regions. This is a relatively underexplored area of tumor biology, but as more high-resolution studies report heterogeneity in the TME and associations with tumor genetics (Lomakin et al, 2021; Mitra et al, 2020), Perturb-map can provide a valuable means for causal studies to determine how particular genes influence local and distal regions of a tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation